Exploring the Lifestyle of Adolescent Girls in Purchasing Korean Skincare Products - Meilyana, Meilyana; Anggriani, Rini; Jati, L. Jatmiko; Wardi, Putri Amalia (ProBisnis : Jurnal Manajemen, 2025)
The beauty industry specifically the consumption of skincare products, has undergone a significant transformation which impacted by Korean Culture (Hallyu). In Indonesia, this transformation has become a trend that affected the lifestyle of teenage girls in choosing their skincare. This study is designed to investigate the consumption pattern of Korean skincare on teenage girls by highlighting the possible factors that impacting the purchase. This research applies the qualitative phenomenological approach, involving six informants aged 18-21 years in Mataram City, West Nusa Tenggara. Data were collected through in-depth interviews and analyzed using condensation techniques, data presentation, and conclusion drawing. The findings reveal that teenage girls consumption of Korean skincare is influenced by three main factors such as appearance needs, promotional effects, and risks anticipation. Teenage girls perceive skincare as part of their self-image and confidence; while social media and influencers play the main roles to introduce and promote the product. Although they are affected by trends, they remain selective by considering product compatibility with their skin type and reading user reviews before making a purchase. The study concludes that Korean skincare consumption among teenage girls is not solely driven by aesthetic considerations but also by awareness of product safety and quality. These findings have implications for the beauty industry, particularly in developing experience-based marketing strategies and providing more in-depth consumer education for the purchasers.